TRANSFORMASI DIGITAL EDUKASI PENGELOLAAN SAMPAH DAN BUDIDAYA MAGGOT DI RUMAH EDUKASI YAYASAN TIGABE RANCAEKEK, BANDUNG - Gema Safitri, Aila gema; Fauzi, Muhammad; Suryan, Ahmad (Universitas Padjadjaran, 2024)
Tigabe Foundation was established in April 2022 and is located in Rancaekek Kencana Village, Bandung Regency. This foundation focuses on social and environmental issues, particularly waste management. One of its contributions to addressing waste issues is through the “Rumah Edukasi” program. Tigabe volunteers, consisting of 3-4 foundation members and administrators, educate the community on maggot-based waste processing. However, the program faces several challenges, including limited volunteers, restricted coverage areas, limited participants, and inadequate waste processing and maggot cultivation tools. This community service program aims to assist Tigabe volunteers in educating the community on waste management. The activities include: (1) discussions with Tigabe Foundation to understand their needs and challenges, (2) developing digital educational content, (3) providing waste processing tools and machines, (4) creating a web- and mobile-based educational application, (5) introducing the application to partners, and (6) mentoring partners in using the application for community education. The main outcomes of this program are: (1) additional educational tools for waste processing, such as bucket composting (emberization) and a shredding machine for organic waste “Sisa Olah Dapur” (SOD), (2) the development of a mobile application